Roles of type 1 regulatory T (Tr1) cells in allergen-specific immunotherapy - Matsuda, Masaya; Terada, Tetsuya; Kitatani, Kazuyuki; Kawata, Ryo; Nabe, Takeshi (Frontiers in Allergy, 2022)
Allergen-specific immunotherapy (AIT) is the only causative treatment for allergic diseases by modification of the immune response to allergens. A key feature of AIT is to induce immunotolerance to allergens by generating antigen-specific regulatory T (Treg) cells in allergic patients. Type 1 regulatory T (Tr1) cells and forkhead box protein 3 (Foxp3)-expressing Treg cells are well known among Treg cell subsets. Foxp3 was identified as a master transcription factor of Treg cells, and its expression is necessary for their suppressive activity. In contrast to Foxp3+ Treg cells, the master transcription factor of Tr1 cells has not been elucidated. Nevertheless, Tr1 cells are generally considered as a distinct subset of Treg cells induced in the periphery during antigen exposure in tolerogenic conditions and can produce large amounts of anti-inflammatory cytokines such as interleukin-10 and transforming growth factor-β, followed by down-regulation of the function of effector immune cells independently of Foxp3 expression. Since the discovery of Tr1 cells more than 20 years ago, research on Tr1 cells has expanded our understanding of the mechanism of AIT. Although the direct precursors and true identity of these cells continues to be disputed, we and others have demonstrated that Tr1 cells are induced in the periphery by AIT, and the induced cells are re-activated by antigens, followed by suppression of allergic symptoms. In this review, we discuss the immune mechanisms for the induction of Tr1 cells by AIT and the immune-suppressive roles of Tr1 cells in AIT.